An Analysis of Firing Time Scatter Effects on Vibration Simulations from Waveforms with Low and High Frequency Components - Randall M. Wheeler (International Society of Explosives Engineers, 1991)
Many blasting companies are using simulated production ground vibration waveforms to aid them in the control of their vibration effects. The simulations are typically produced by using a seismograph to record a signature waveform from a single hole shot and subsequently applying the various delays to be used in a proposed production design. The ability of this simulation method to give good results usually depends on three primary factors. These are: 1) the homogeneity of the seismic travel path from hole to hole; 2) the consistency of the seismic energy release per unit of explosive from hole to hole; and 3) whether or not the delays fire as planned.